STEVE REICH’S STYLE AND COMPONISTIC CONCEPTS REFLECTED IN TEHILLIM SCORE - BELIBOU, Alexandra (Studia Universitatis Babes-Bolyai Musica, 2023)
The present article traces the way compositional conceptions and writing style are highlighted in the creation of Tehillim belonging to one of the most prolific contemporary composers – Steve Reich. The research starts from the composer’s ideas about what the compositional journey means, continues with a musical analysis that emphasizes the ways of development of the musical data, and ends with the observation of how the principles of composing are objectified in realities and musical choices. I chose this score because it differs from the previous ones with original elements, with musical parameters that Reich did not use in his career, so it is very interesting to find the composer’s specific compositional archetypes in this specific work.